Techno fashion through Islamic looking glass / Zolina Mohamad and Tengku Azhari Tengku Azizan - Zolina, Mohamad; Tengku Azhari, Tengku Azizan (Universiti Teknologi MARA, Perak, 2016)
The research project is designated to lead focuses on specific contexts of the proposed topic of Interest. Theoretical framework plus research methodology that strategically function as the core driving mechanism will navigate the research Into specific area of expertise, nonetheless the area of fashion art and Islamic Sociology. Thus both academic disciplines have been selected as my first scientific area of preference. This research project upholds qualitative and quantitative of research method structures. Although the research containment will be thoroughly composed and constructed by using both methodological paradigm, laboratory experimentation will be taken into account in order to obtain coherent research finding.This research project will unravel the genealogy and a brief historical background of the origin of techno fashion, its origin of existence, its functionality, design and aesthetic characteristics and high-tech personality. Throughout fundamental investigation on the techno fashion preliminary profile, the research will continue to scope the research objective Into its original mission, which is to perceive and depict the equivalence and mutual coherency between techno fashion and Islamic Clothing Concept.